Women entrepreneurship in China: where are we now and where are we heading. Issue 1 (1st January 2021) - Cooke, Fang Lee; Xiao, Mengtian
ABSTRACT: Despite the continuing growth in numbers of women entrepreneurs in China since the 1980s, research in this area has not kept pace with the development. In this paper, we critically review the current situation of women's entrepreneurship in China and the status quo of research in this field. We then analyse the political, social, cultural, organizational, and individual barriers women entrepreneurs may encounter, as well as the policy initiatives and institutional and social support to promote women entrepreneurship. We further outline the main theoretical perspectives that have been mobilized to inform research on women's entrepreneurship in China and indicate areas for future studies and how they may be framed. We argue for the need to adopt a more critical approach, such as feminist discourse analysis and a critical socio-technological perspective to inform future research, to shed light on a range of phenomena related to women's entrepreneurship that have yet to receive adequate research attention. Our review has implications for human resource development in China and other societal contexts with similar cultural norms.